THE RISE OF CRITICAL SOCIAL THOUGHT - Lengermann, Patricia; Niebrugge-Brantley, Jill (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The purpose of this course is to introduce you to an important tradition in thehistory of ideas, the rise of critical social thought. Critical social thought is that system ofthinking and ideas which allows individuals to study the social world as a human productwhich can be changed and improved by human effort. Critical thought as a tradition anda practice calls us both to understanding and to action. It is in some measure the sourceof our democracy, our liberty, and our sense of collective responsibility.The course is organized as a lecture/discussion focused on the essential elements ofcritical social thought: (1) the intelligence–and courage--to "see through" the taken-forgrantedarrangements of the everyday world to the processes that produce and reproducethem; (2) the critique of injustice in that everyday world which requires taking the pointof view of less powerful groups, and (3) the quest for strategies to bring about changetoward a more just social world. We explore this tradition of critical social thought byfocusing on some of the major ideas of thinkers who helped create sociology in thenineteenth and early twentieth centuries.